Concentrations and Risk of Polycyclic Aromatic Hydrocarbons (PAHs) in Oil and Tomato-Based Sauces from Selected Brands of Canned Fish Consumed in Nigeria. (9th August 2022) - Iwegbue, Chukwujindu M. A.; Tesi, Godswill O.; Ogbuta, Anthony A.; Lari, Bulouebibo; Igbuku, Ufuoma A.; Obi, Grace; Martincigh, Bice S.
Abstract: The concentrations of the 16 US EPA polycylic aromatic hydrocarbons (PAHs) were investigated in oil and tomato-based sauces from some popular brands of canned fish products (mackerel, sardine and tuna) commonly consumed in Nigeria. The aim of the study was to provide data on the PAH compositions and likely risks arising from ingestion of these oil and tomato-based sauces. The PAH content in these oils and sauces was determined by gas chromatography-mass spectrometry. The concentrations of PAHs in these samples varied from 101 to 698 µg kg −1 for tomato sauces from canned mackerel, 168 to 733 µg kg −1 for oils from canned sardines, and 204 to 459 µg kg −1 for oils from canned tuna. The benzo(a)pyrene and PAH4 (benzo(a)anthracene [BaA] + Chrysene [Chry] + benzo(a)pyrene [BaP] + benzo(b)fluoranthene [BbF]) concentrations in the majority of the samples exceeded their respective limits as specified by the European Union regulations. The benzo(a)pyrene carcinogenic (BaPTEQ ) and mutagenic (BaPMEQ ) potency values ranged from not detected (nd) to 288 µg kg −1 and nd-217 µg kg −1 respectively. The probable cancer risk arising from consumption of oils and tomato sauces from these canned fish products were above the acceptable risk value of 10 −6, which indicates that there is a considerable risk associated with the consumption of sauces and oils from these canned fish products.